2021
DOI: 10.2174/1567202618666210927095613
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischaemic Stroke Incidence after Coronavirus Vaccine in Indonesia: Case Series

Abstract: Background: Coronavirus disease-19 (COVID-19) is an infectious disease with high morbidity and mortality rates. Indonesia had reported a 2.8% of mortality rate up to June 2021. A strategy to control the virus spreading is by vaccination. The Indonesian Food and Drug Monitoring Agency had approved the use of CoronaVac, an inactivated virus vaccine developed by Sinovac. Most adverse events following immunization (AEFI) for CoronaVac are mild, and the most common symptoms are injection-site pain, headache, and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“… 5 , 6 Some case reports also describe ischaemic stroke and thrombotic events after CoronaVac vaccination. 7 , 8 Nonetheless, evidence of post-vaccination adverse events in older adults beyond case reports is still scarce. Although randomised controlled trials of CoronaVac have not shown major adverse events after vaccination, 9 , 10 they only included a small proportion of older participants and were not able to evaluate rare events due to small numbers of events.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Some case reports also describe ischaemic stroke and thrombotic events after CoronaVac vaccination. 7 , 8 Nonetheless, evidence of post-vaccination adverse events in older adults beyond case reports is still scarce. Although randomised controlled trials of CoronaVac have not shown major adverse events after vaccination, 9 , 10 they only included a small proportion of older participants and were not able to evaluate rare events due to small numbers of events.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, efficacies of BBIBP-CorV against symptomatic infection and hospitalization were both 79%, according to WHO [ 56 ]. Although common side effects of these two vaccines are mild to moderate [ 57 , 58 ], there are rare cases of thrombotic events [ [59] , [60] , [61] , [62] ]. As presented in Table 3 , we found 2 articles including 4 patients (3 CoronaVac and 1 BBIBP-CorV) with AIS after inactivated virus vaccine administration.…”
Section: Resultsmentioning
confidence: 99%
“… Author(s) No. of cases vaccine dose Age gender Past medical history/medication(s) Time from vaccination (days) Clinical presentation Imaging findings Lab findings Treatment/outcome BIBP (Sinopharm) G. Elaidouni et al [ 60 ] 1 First 36 male HTN, DM, dyslipidemia, smoker/clopidogrel 2 headaches, left hemiplegia, left facial paralysis, left hemibody hypotonia, impaired consciousness superficial and deep right parietal infarction Platelets count and D-dimer: NL ASA, Enoxaparine/alive Sinovac R. Hidayat et al [ 61 ] 3 First 77 male CAD, DM, HTN, ischemic stroke 0 left lower limb hemiparesis, slurred speech several infarctions in bilateral centrum semiovale, cortical-subcortical right frontal and temporal lobe, bilateral external capsule, and right pons Platelets count: NL ASA, Clopidogrel/alive First 79 male HTN, hypercholesterolemia, ex-smoker 2 left hemiparesis lacunar infarcts in right frontoparietal region Platelets count: NL ASA/alive First 62 male HTN, ischemic stroke 1 left hemiparesis, slurred speech, and facial asymmetry watershed infarctions in right centrum semiovale and corona radiata Platelets count: NL, normal D-dimer ASA, Clopidogrel/alive NL: normal; N/A: not available; DM: diabetes mellitus; HTN: hypertension; CAD: coronary artery disease; ASA: acetylsalicylic acid (aspirin). …”
Section: Resultsmentioning
confidence: 99%
“…6 However, arterial and venous thromboembolic events have been reported, and few cases of ischemic stroke have been linked mostly with not RNAbased COVID-19 vaccines. [7][8][9][10][11][12] Multifactorial pathways may contribute to the onset of cerebral thrombosis after COVID-19 vaccination. On first principles, we could not differentiate atherosclerotic thrombosis as opposed to immune-mediated primary inflammatory arterial thrombosis upon clinical, laboratory, and imaging findings.…”
mentioning
confidence: 99%
“… 6 However, arterial and venous thromboembolic events have been reported, and few cases of ischemic stroke have been linked mostly with not RNA‐based COVID‐19 vaccines. 7 , 8 , 9 , 10 , 11 , 12 …”
mentioning
confidence: 99%